CT and MRI features of tumors and tumor-like lesions in the abdominal wall - Li, Meng; Zhang, Li; Xu, Xiao-Juan; Shi, Zhuo; Zhao, Xin-Ming (Quantitative Imaging in Medicine and Surgery, 2019)
Masses involving the abdominal wall are common in clinical practice and have many etiologies, including tumors and tumor-like lesions. Abdominal wall tumors include primary and secondary tumors, the former of which constitute a heterogeneous group of soft tissue tumors with their own unique spectrum. Tumor-like lesions, such as hernias, are more common and must be distinguished from true tumors. Medical imaging is valuable for discovering, diagnosing, and evaluating the extent of abdominal wall masses. With the increasing application of computed tomography (CT) and magnetic resonance imaging (MRI), determining a diagnosis or narrowing the differential diagnosis is often possible, thus facilitating effective management. In this article, we comprehensively review the spectrum of common abdominal wall masses and present the CT and MRI features of typical cases in our hospital. A systematic stepwise diagnostic approach is also proposed for clinical practice.